Trifecta and pentafecta outcomes following robot-assisted partial nephrectomy for hilar versus nonhilar tumors: A propensity-matched analysis - Shantanu Tyagi; Gopal Sharma; Girdhar S Bora; Ravimohan S Mavuduru; Aditya Prakash Sharma; Sudheer Kumar Devana; Ujjwal Gorsi; Nandita Kakkar; Shrawan K Singh (Indian Journal of Urology, 2021)
Introduction: Hilar tumors are a unique subset of complex renal masses posing a potential surgical challenge during partial nephrectomy. The outcomes of hilar masses have not been compared to non-hilar renal masses of similar RENAL nephrometry score (RNS). In this study, we analyzed the outcomes of hilar versus nonhilar masses after a propensity score matching. Methods: Prospectively maintained database of patients who underwent robot assisted PN between November 2014 and December 2018 was abstracted for hilar and nonhilar tumors. We performed propensity matching for baseline variables such as age, sex, body mass index, comorbidities, preoperative glomerular filtration rate, and RNS for each patient on the basis of propensity scores. Results: We included 48 patients with hilar tumors and 153 with nonhilar tumors. On propensity matching, 41 patients were included in each group. The mean operative time (162.4 ± 48.9 min vs. 144.1 ± 38.8 min, P = 0.48), warm ischemia time (29.0 ± 8.8 min vs. 24.4 ± 8.2 min, P = 0.12), and the estimated blood loss (201.8 ± 184.7 ml vs. 150.6 ± 160.5 ml, P = 0.37) were not significantly different between the hilar and the nonhilar groups. Trifecta was achieved in only 14/41 (34.1%) of the patients in the hilar group as compared to 24/41 (58.5%) in the nonhilar group (P = 0.027). Logistic regression analysis identified that hilar location of the tumors was not an independent predictor of overall complications (OR 6.37, confidence interval [CI] 0.5–69.4, P = 0.4), trifecta (OR 0.38, CI 0.14–1.0, P = 0.051), and pentafecta outcomes (OR 0.4, CI 0.1–1.51, P = 0.17). Conclusions: Hilar location was associated with poorer trifecta outcomes compared to the nonhilar tumors. However, hilar location per se was not an independent predictor of overall complications and trifecta and pentafecta outcomes.